Rancang Bangun Aplikasi Customer Relantionship Management (CRM) Dengan Metode Double Exponential Smoothing Pada CV. Mulia Sejahtera - Putu Ayu Lestari; I Gede Putu Krisna Juliharta; Ni Made Estiyanti (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2019)
CV. Mulia Sejahtera is one of the companies that pay attention to the customer satisfaction. In accordance with the company tagline which is "Serve and Care" that means to serve and care about customer satisfaction. The company is still using the manual method of recording in the transactional processes of the company. To speed up the process of transactional companies with a high response rate to the customer and assist management in decision- making needed an application that could help the company. The Customer Relationship Management (CRM) is a marketing strategy to create and maintain a good relationship with the customers in the form of applications Information technology (IT). The Web based e-CRM application can manage customer data, product promotion, product demand data and management level of satisfaction of the customer in order to create a good relationships with customers. Equipped with Double Exponential Smoothing method in predicting the sales on this website will assist management in making decisions faster. With the implementation of this application, is expected to maintain a good relationship with customers and gain a new customers, it will bring a lot of benefits to the company